2008
DOI: 10.1021/jf801626f
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on 3-Mercaptohexanol (3MH) Biogenesis in Sauvignon Blanc Wines: Cys-3MH and (E)-Hexen-2-al Are Not the Major Precursors

Abstract: The molar conversion yield of Cys-3MH into 3MH, during alcoholic fermentation, was traced using a deuterated isotope of the precursor added to different Sauvignon Blanc musts. This yield is close to that found in synthetic media supplemented with synthetic Cys-3MH, that is, below 1%. Yet, this represents only 3-7% of the total 3MH production in wine. This clearly shows that Cys-3MH is a precursor of 3MH, but not the main one in the different musts tested. The contribution of ( E)-hex-2-enal, which has been sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(111 citation statements)
references
References 30 publications
6
104
1
Order By: Relevance
“…It has been shown more recently that glutathione precursors are an equally, if not more important, source of these pleasant smelling polyfunctional thiols (Subileau et al 2008, Fedrizzi et al 2009, Grant-Preece et al 2010, Roland et al 2010, Winter et al 2010. A recent study documented that the glutathione-conjugated 3MH diastereomers were up to 35 times more abundant than their cysteineconjugated counterparts in juices of Sauvignon blanc, Riesling, Chardonnay, and Pinot Grigio; Sauvignon blanc juices generally had the highest concentrations of the varieties studied .…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 96%
See 2 more Smart Citations
“…It has been shown more recently that glutathione precursors are an equally, if not more important, source of these pleasant smelling polyfunctional thiols (Subileau et al 2008, Fedrizzi et al 2009, Grant-Preece et al 2010, Roland et al 2010, Winter et al 2010. A recent study documented that the glutathione-conjugated 3MH diastereomers were up to 35 times more abundant than their cysteineconjugated counterparts in juices of Sauvignon blanc, Riesling, Chardonnay, and Pinot Grigio; Sauvignon blanc juices generally had the highest concentrations of the varieties studied .…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 96%
“…A main research focus has been on the release of polyfunctional thiols during fermentation, due primarily to the fact that yeasts have limited and varied capacity to liberate the polyfunctional thiols from their precursors (Subileau et al 2008, Winter et al 2011. For example, estimates from the literature vary from 0.1 to 12% conversion of cysteine-3MH to 3MH (and 3MHA) (Subileau et al 2008), representing only a small fraction of the polyfunctional thiols present in juice and leaving significant pools of both cysteine and glutathione precursors in finished wines .…”
Section: Volatile Sulfur Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some precursors in the juice have been identified as being cysteinylated or glutathionylated precursors (Tominaga et al, 1998b;Peyrot des Ganchos et al, 2002;Fedrizzi et al, 2009). However, studies have shown that these precursors account for only a fraction of the total amount of thiols present in the wine (Subileau et al, 2008a;Roland et al, 2010a;2010b), and no direct correlation between precursor concentration and the amount of free volatile thiols in the resulting wines has been observed Roland et al, 2011;Pinu et al, 2012). Other than release from precursors, the biogenesis of volatile thiols also has been proposed.…”
Section: Volatile Thiolsmentioning
confidence: 99%
“…However, several researches have indicated that no clear correlation between precursor concentrations in must and free thiol concentration in wine exist [8,16,59,73,80,[85][86][87][88][89].…”
Section: Varietal Thiol Precursorsmentioning
confidence: 99%